Plant-based secondary metabolites as natural remedies: a comprehensive review on terpenes and their therapeutic applications - Khanam, Sheeba; Mishra, Pooja; Faruqui, Tabrez; Alam, Pravej; Albalawi, Thamer; Siddiqui, Faiza; Rafi, Zeeshan; Khan, Salman (Frontiers in Pharmacology, 2025)
Terpenes are among the most diverse kinds of natural products because of their remarkable chemical variety. Numerous biological characteristics of terpenoids have been documented, including their antibacterial, antifungal, antiviral, antihyperglycemic, anti-inflammatory, and antiparasitic effects, as well as their cancer chemopreventive benefits. Additionally, terpenes are utilized in the manufacturing of organic solvents, varnishes, inks, adhesives, synthetic polymers, natural rubbers, cleaning supplies, biofuels, insecticides, and food and beverage items. Terpenes are therefore highly valued in modern medicine, pharmacy, nutraceuticals, cosmetics, and other fields. Plant oils, including terpenes, have been used to treat a variety of diseases without a full understanding of the roles or modes of action of particular bioactive substances. Many of these compounds are only present in nature in extremely small amounts; thus, methods such as metabolic engineering and synthetic biology are used to harvest them in large quantities in order to produce enough medicine. This comprehensive review aims to elucidate the biochemistry, phytochemical properties, and pharmacological activities of terpenes in metabolic disorders.